2016
DOI: 10.1371/journal.pone.0163547
|View full text |Cite
|
Sign up to set email alerts
|

From Human Geography to Biological Invasions: The Black Rat Distribution in the Changing Southeastern of Senegal

Abstract: In the contemporary context of zoonosis emergence and spread, invasive species are a major issue since they represent potential pathogen hosts. Even though many progresses have been done to understand and predict spatial patterns of invasive species, the challenge to identify the underlying determinants of their distribution remains a central question in invasion biology. This is particularly exacerbated in the case of commensal species that strictly depend on humankind for dispersal and perennial establishmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Deviations from the main genetic pattern resulting from historical processes can be attributed to the current heterogeneity of the cityscape in terms of habitat quality for the house mouse (Adrichem et al, 2013;Byers et al, 2019;Combs et al, 2018a,b;Lambert et al, 2017;Lucaccioni et al, 2016;Masi et al, 2010;Santos et al, 2017). Spatial variations in the level of genetic differentiation are often interpreted as reflecting the presence of physical barriers to individual dispersal, while they may actually result from variations in effective population size, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deviations from the main genetic pattern resulting from historical processes can be attributed to the current heterogeneity of the cityscape in terms of habitat quality for the house mouse (Adrichem et al, 2013;Byers et al, 2019;Combs et al, 2018a,b;Lambert et al, 2017;Lucaccioni et al, 2016;Masi et al, 2010;Santos et al, 2017). Spatial variations in the level of genetic differentiation are often interpreted as reflecting the presence of physical barriers to individual dispersal, while they may actually result from variations in effective population size, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Such genetic breaks have been attributed to physical barriers to dispersal (waterway in Baltimore, USA -Gardner-Santana et al, 2009; roads and topography in Pau de Lima, Salvador, Brazil -Kajdacsi et al, 2013;Richardson et al, 2017) or spatial heterogeneity in habitat quality that impacts local population size (resource availability varying with socioeconomic features of urban infrastructures, Manhattan, USA -Combs et al, 2018b). The need to integrate socioeconomic features of the urban environment in population dynamic and genetic studies of commensal rodents is advocated by previous works that have shown that areas with poor housing conditions (including building material quality, sanitation status within and outside the houses) and commercial premises are more prone to rodent infestations than high-standing residential or touristic areas (Adrichem et al, 2013;Byers et al, 2019;Combs et al, 2018a;Jassat et al, 2013;Lambert et al, 2017;Lucaccioni et al, 2016;Masi et al, 2010;Santos et al, 2017). In addition to current features, spatial genetic patterns may also reflect past demographic events related to cityscape evolution during the historical timeframe of urbanization Lourenço et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Soutouta (SOU) and Boutougoufara (BOU) are marginal rural localities that have undoubtedly been colonized very late by R . rattus , because their connection to commercial networks dates from 2007 [ 92 , 93 ]. Conversely, Kedougou (KED) and Badi Nieriko (BAN) were colonized by R .…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe signs of disease in the infected animals at the time of capture. Of the 4 villages that yielded the highest numbers of black rats in this study, 3 harbored rats infected with SEOV ( Figure 2 ) ( 7 ). High densities of black rats might contribute to the occurrence of hantavirus in these villages, especially because host demography might affect hantavirus circulation ( 13 ).…”
Section: The Studymentioning
confidence: 90%
“…Southeastern Senegal has become a major trade area because of urbanization and substantial improvement of its road and rail networks in the late 1990s (7). Within a few years, these changes led to the rapid spread of a major invasive rodent species, the black rat (Rattus rattus [family Murinae]), which is a reservoir for Seoul orthohantavirus (SEOV) (4,5,7). To assess the prevalence of hantaviruses in rodents, we screened for hantaviruses in R. rattus rats and commensal or peridomestic co-existing rodents in 2012-2013, approximately 15 years after the 1998 opening of a tarred road in eastern Senegal.…”
Section: Dispatchesmentioning
confidence: 99%